The atrial natriuretic peptide (ANP) knockout mouse does not exhibit the phenotypic features of pre-eclampsia or demonstrate fetal growth restriction. (June 2016) - Finn-Sell, Sarah L.; Renshall, Lewis J.; Cowley, Elizabeth J.; Dilworth, Mark R.; Wareing, Mark; Greenwood, Susan L.; Sibley, Colin P.; Cottrell, Elizabeth C.
Abstract: The ANP knockout mouse is reported to exhibit pregnancy-associated hypertension, proteinuria and impaired placental trophoblast invasion and spiral artery remodeling, key features of pre-eclampsia (PE). We hypothesized that these mice may provide a relevant model of human PE with associated fetal growth restriction (FGR). Here, we investigated pregnancies of ANP wild type (ANP +/+ ), heterozygous (ANP +/- ) and knockout (ANP −/- ) mice. Maternal blood pressure did not differ between genotypes (E12.5, E17.5), and fetal weight (E18.5) was unaffected. Placental weight was greater in ANP −/− versus ANP +/+ mice. Therefore, in our hands, the ANP model does not express phenotypic features of PE with FGR. Highlights: Mouse models of pre-eclampsia and fetal growth restriction are needed to test potential therapies. ANP knockout mice have previously been identified as a potential model of pre-eclampsia. We find that these mice do not exhibit pregnancy-associated hypertension, or fetal growth restriction. ANP knockout mice do not provide a robust model of pre-eclampsia or fetal growth restriction.